The 'super-resolution' revolution. (21st September 2009) - Davis, Ilan
Abstract : We are currently in the midst of an exciting revolution in microscopy. In many ways, this has been happening for several decades, but it is the rate of development of new methods that has increased recently. The last few years have seen an impressive proliferation of new instruments for imaging at higher resolution, imaging single molecules and faster and more sensitive multidimensional live cell imaging. These include light sheet microscopy, stimulated emission depletion, structured illumination and live cell imaging on the OMX (optical microscopy experimental) platform. However, new probes and image analysis methods have also been crucial for the development of these revolutionary methods.